Humoral immune response of water buffalo monitored with three different antigens of Toxocara vitulorum - de Souza, E. M.; Starke-Buzetti, W. A.; Ferreira, F. P.; Neves, M. F.; Machado, R. Z. (Elsevier B.V., 2004)
Humoral immune response of water buffalo naturally infected with Toxocara vitulorum was monitored using three different antigens of this parasite in serum and colostrum of buffalo cows and calves. Soluble extract (Ex) and excretory/secretory (ES) larval antigens and perienteric fluid antigen (Pe) of adult T vitulorum were used to measure the antibody levels by an indirect ELISA. Serum of 7-12 buffalo cows for the first 365 days and colostrum of the same number of buffalo cows for the first 60 days of parturition, and serum of 8-10 buffalo calves for the first 365 days afterbirth were assayed. The ELISA detected antibodies against all three T vitulorum antigens in the colostrum and serum of 100% of buffalo cows and calves examined. The highest antibody levels against Ex, ES and Pe antigens were detected in the buffalo cow sera during the perinatal period and were maintained at high levels through 300 days after parturition. on the other hand, colostrum antibody concentrations of all three antigens were highest on the first day post-parturition, but decreased sharply during the first 15 days. Concomitantly to the monitoring of immune response, the parasitic status of the calves was also evaluated. In calves, antibodies passively acquired were at the highest concentrations 24 h after birth and remained at high levels until 45 days coincidentally with the peak of T vitulorum infection. The rejection of the worms by the calves occurred simultaneously with the decline of antibody levels, which reached their lowest levels between 76 and 150 days. Thereafter, probably because of the presence of adults/larvae stimulation, the calves acquired active immunity and the antibodies started to increase slightly in the serum and plateaued between the days 211 and 365. All three antigens were detected by the serum antibodies of buffalo calves; however, the concentration of anti-Pe antibody was higher than anti-EX and anti-ES, particularly after 90 days of age. By conclusion, the buffalo cows develop immunity and keep high levels of antibodies against T vitulorum-Ex, ES and Pe antigens and these antibodies are transferred to their calves through the colostrum. This passively acquired immunity does not protect the calves against the acquisition of the infection, but these antibodies, passively or actively acquired, may have an important role during worm rejection by the calves and prevention of intestinal reinfection. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Toxocara vitulorum; water buffalo; ELISA